Genomic studies of multiple myeloma reveal an association between X chromosome alterations and genomic profile complexity. Issue 1 (18th August 2016) - Sticca, Tiberio; Caberg, Jean‐Hubert; Wenric, Stephane; Poulet, Christophe; Herens, Christian; Jamar, Mauricette; Josse, Claire; El Guendi, Sonia; Max, Stéphanie; Beguin, Yves; Gothot, André; Caers, Jo; et al.
Abstract : The genomic profile of multiple myeloma (MM) has prognostic value by dividing patients into a good prognosis hyperdiploid group and a bad prognosis nonhyperdiploid group with a higher incidence of IGH translocations. This classification, however, is inadequate and many other parameters like mutations, epigenetic modifications, and genomic heterogeneity may influence the prognosis. We performed a genomic study by array‐based comparative genomic hybridization on a cohort of 162 patients to evaluate the frequency of genomic gains and losses. We identified a high frequency of X chromosome alterations leading to partial Xq duplication, often associated with inactive X (Xi) deletion in female patients. This partial X duplication could be a cytogenetic marker of aneuploidy as it is correlated with a high number of chromosomal breakages. Patient with high level of chromosomal breakage had reduced survival regardless the region implicated. A higher transcriptional level was shown for genes with potential implication in cancer and located in this altered region. Among these genes, IKBKG and IRAK1 are members of the NFKB pathway which plays an important role in MM and is a target for specific treatments. © 2016 Wiley Periodicals, Inc.